ANALISA PANJANG ANTRIAN DAN TUNDAAN PADA SIMPANG EMPAT JALAN D.I PANJAITAN 1 – JALAN D.I PANJAITAN 2 – JALAN GUNUNG LINGAI – JALAN PM. NOOR - DRA, HEN (KURVA S JURNAL MAHASISWA, 2014)
Along with the rapid development of the city, traffic demands of an increasingly crowded require attention and the work assessment for conditions intersection. Unbalance amount of traffic flow with the effective width of the road, the low level of service, as well as the short time the green will cause delays and queues of traffic at the intersection.As the above, try to conduct a study on the queue with a delay at signalized intersection.This study uses the approach Manual Kapasitas Jalan Indonesia (MKJI) in 1997, to get the value of queues, delays and long queues to review the case of the intersection of street D.I Panjaitan 1 - street D.I Panjaitan 2 - street Gunung Lingai - street PM. Noor Samarinda.The results of the field shows the degree of saturation on-closers closers these intersections ranged from 0.901 to 0.924, this shows that the shape of the intersection hardly worth operationalized.After the equation is obtained, then retrieved a comparison value at peak hours with the condition showed a decrease in the performance of the junction.Besides the low discipline of road users causing malfunctions roads, and lack of sharpness officials on the ground to make the intersection of performance decreases on the other street vendors who sell dibadan roads causing can not be used to the maximum by road users.As a suggestion for the need for solutions such as: changes in shape of the intersection or phase-change time changes green or partially redirect traffic to the road public transport alternatives.